Does cognitive behaviour therapy for insomnia reduce repetitive negative thinking and sleep-related worry beliefs? A systematic review and meta-analysis. (February 2021) - Ballesio, Andrea; Bacaro, Valeria; Vacca, Mariacarolina; Chirico, Andrea; Lucidi, Fabio; Riemann, Dieter; Baglioni, Chiara; Lombardo, Caterina
Summary: Repetitive negative thinking (RNT), i.e., worry, rumination, and transdiagnostic repetitive thinking, is thought to exacerbate and perpetuate insomnia in cognitive models. Moreover, RNT is a longitudinal precursor of depression and anxiety, which are often co-present alongside insomnia. Whilst accumulating evidence supports the efficacy of cognitive behavioural therapy for insomnia (CBT-I) in reducing depression and anxiety symptoms, the literature on the effects of CBT-I on RNT has never been systematically appraised. Importantly, preliminary evidence suggests that reduction of RNT following CBT-I may be associated with reduction of depression and anxiety. Therefore, we aimed to conduct a systematic review and meta-analysis on the effects of CBT-I on RNT. Seven databases were searched, and 15 randomised controlled trials were included. Results showed moderate-to-large effects of CBT-I on worry (Hedge's g range: −0.41 to g = −0.71) but small and non-reliable effects on rumination (g = −0.13). No clear evidence was found for an association between post-treatment reduction in RNT and post-treatment reduction in depression and anxiety. Although the literature is small and still developing, CBT-I seems to have a stronger impact on sleep-related versus general measures of RNT. We discuss a research agenda aimed at advancing the study of RNT in CBT-I trials.